2022
DOI: 10.2151/sola.2022-019
|View full text |Cite
|
Sign up to set email alerts
|

Meteotsunamis in Japan Associated with the Tonga Eruption in January 2022

Abstract: Large-amplitude meteotsunamis were observed in many areas in Japan, following the arrival of barometric Lamb waves emitted by an underwater volcanic eruption of Hunga Tonga-Hunga Ha'apai in January 2022. We modeled the power spectra of the tidal level data obtained from 12 tide stations of the Geospatial Information Authority of Japan, based on a method of transfer function which converts the barometric pressure pulse spectra into the meteotsunami spectra. The obtained transfer functions are similar at 12 stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The coincident occurrence of atmospheric and ionospheric perturbations indicates the instantaneous ionospheric response to atmospheric perturbations. One might suggest that these atmospheric and ionospheric perturbations were associated with tsunamis, but tsunamis were detected around Japan after 15 UT (Kataoka et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The coincident occurrence of atmospheric and ionospheric perturbations indicates the instantaneous ionospheric response to atmospheric perturbations. One might suggest that these atmospheric and ionospheric perturbations were associated with tsunamis, but tsunamis were detected around Japan after 15 UT (Kataoka et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Again, taking the propagating pressure pulses clearly visualized by the Soretena weather stations and the angular distance of each station from the Tonga volcano, ref. [21] estimated the phase speed of the first Lamb wave to be 310 m/s with the dominant wavelength of 500-600 km. In the end, the vertical TEC (vTEC) was used to study the medium scale traveling ionospheric disturbances (MSTIDs) and the large-scale traveling ionospheric disturbances (LSTIDs).…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric perturbation circled the Earth at least three times, triggering an oceanic response that was recorded at many locations around the world, in what can be called a global meteotsunami. The magnitude of the ocean response was only hazardous in the Pacific Ocean, where SLOs were produced by different sources and not only by the atmospheric disturbance, as explored in other studies [15][16][17][18]20,21 . Therefore, the singularity of this event does not rely on the large amplitude of the observed SLOs, but on the fact that a distant volcano explosion generated a noticeable sea level response worldwide.…”
Section: Discussionmentioning
confidence: 83%
“…gov/ hazel/ view/ hazar ds/ tsuna mi/ relat ed-runups/ 5824); the amplitude of the recorded SLOs ranged from a few centimeters up to 1-2 m at some tide gauges of Japan and the West Coast of the USA, Mexico, Chile and Peru 14 . Studies combining the analysis of observations with numerical simulations have identified that, in the Pacific Ocean, the observed SLOs could be attributed to three different processes: (i) the long (tsunami) waves generated by the collapse of the volcano; (ii) the sea level response to an atmospheric shock wave in the vicinity of the volcano; and (iii) the sea level response to the atmospheric Lamb waves that propagated far from the source [15][16][17][18][19][20] . The overlapping of the three processes made that in the Pacific Ocean SLOs were significantly larger than in the rest of the globe.Away from the Pacific Ocean, SLOs would be entirely related to the propagation of the atmospheric Lamb waves.…”
mentioning
confidence: 99%